A Survey of Attack Mechanisms on Infrastructure-Mode 802.11 Wireless Networks and Their Detection (2015)
The 802.11 wireless network revolution has not come without trouble. Since their creation, wireless networks have been plagued with security problems, derived from poor initial design of 802.11 security mechanisms, accelerated deployment and adoption of the technology, and lack of user education. The goal of this article is to present the reader with a survey of the currently documented detectable attacks to infrastructure-mode 802.11 wireless networks, and a proposal of mechanisms and metrics that can be used to detect such attacks. The attacks and their detection methods are divided in seven categories: Denial-of service, traffic analysis attacks, passive eavesdropping, attacks against WEP, attacks against WPA and WPA2 in pre-shared key (PSK) and Enterprise modes, and man-in-the-middle attacks.